A study on the reliability of the ladao template as a baseline in the set-up of maxillary teeth in denture construction - Ambrosio, April Rose U.; Ladao, Jake (Adviser).
Reliability of the Ladao Template as a baseline in the set-up of maxillary teeth in denture construction was studied. 10 students from each year level of the UPCD were used a samples. Criteria for the selection of samples were that they have complete natural dentition from the central incisors to the second molars in the upper arch, that they have never had any orthodontic treatment, and that the teeth are well-aligned in the dental arch. Alginate impressions were made of the subjects' upper arch and five reference points (the midline from a point midway between the 2 central incisors, cusp tips of the right and left canines, mesiobuccals cusp tips of the right and left first permanent molars) were marked on the casts obtained before having the casts xeroxed. The photocopies of the casts were the ones used in the measurement of the bicanine diameter, bimolar diameter, arch length, antero-posterior length and arc radius. The measurements were done 3 times and the averages were computed. Of the 5 variables studied, arc radius and antero-posterior length were subjected to Statistical Analysis basing the hypothesized values on previous studies. Results showed that for the arc radius, the computed mean is 22.87 as compared to the hypothesized value which is 24 mm. It was found that at 95% confidence level, the hypothesis that the arc falls within a circle with a 24 mm radius can not be refuted. For the antero-posterior length, the computed mean is 7.8mm. as compared to the hypothesized value which is 9 mm. It was also founf out that 95% confidence level, there is sufficient evidence to accept the hypothesis that the antero-posterior length is equal to 99 mm. The rest of the variables were not analyzed there being no available baseline data for Filipinos. The following values are recommended as baseline data for future studies: bicanine diameter: 35 mm., bimolar diameter: 53 mm., arch length: 28 mm.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Dentures